(untitled) (Teacher Education through Flexible Learning in Africa (TETFLE), 2021)
Various studies on literacy have been conducted worldwide, but there is paucity of studies that explored adult literacy from the perspectives of African traditional values. Many African communities, including Rwanda, still experience a low level of literacy in the 21st century. As a contribution to address this literacy gap, an innovative model coined “Eclectic Traditional Value Hub Model” is being implemented in selected Rwandan rural communities to promote quadriliteracy, community literacy and digital literacy among adults with limited literacy. The newness of this model is twofold: firstly, it draws from a range of African and Rwandan traditional values; secondly, it boosts parallel literacy practices in four languages, namely Kinyarwanda, English, French and Kiswahili, by which it is described as “Four-in-One”. This study reports on one year’s implementation of this model, exploring its level of success in accelerating quadriliteracy and community digital literacy and numeracy among Rwandan communities. Participants include University of Rwanda lecturers who initiated the model, graduates from secondary schools who are literacy trainers in their local communities and trainees who are citizens with limited literacy including motorists, street vendors, small-sized business people and others who strive to uplift their literacy levels. The successful stride of this model is that about ten thousand community members from Eastern province are accelerating their literacy practices through translingual and cross-lingual practices. We recommend the application of this model to other African settings with more African traditional values and assess its impact in minimising the high illiteracy rate reported in various corners of Africa.